Psychological Hardiness and its Relationship to some Demographic Variables among Post-Basic Education Teachers in the Governorate of South Al-Batinah in the Sultanate of Oman - Yousuf S. Al Rujaibi; Mohamad A. Al Shaikh Hammoud (Sultan Qaboos University, 2018)
This study aimed to identify the level of psychological hardiness and its relationship to some demographic variables among post-basic education teachers in the Governorate of South Al-Batinah in the Sultanate of Oman. The sample of the study, which was chosen based on the stratification random method, consisted of 306 teachers; 178 males and 128 females. In order to achieve the aims of the study, a descriptive correlational approach was used, and the psychological hardiness scale was developed by the researchers and administered to the study sample after assessing its psychometric properties. The results of this study showed that the level of psychological hardiness among post-basic education teachers in the Governorate of South Al-Batinah was high as the mean score of psychological hardiness was 2.44/3. Additionally, there were no statistically significant differences at the 0.05 level in psychological hardiness due to gender, major and teaching experience.